Extreme Multi-label Learning with Label Features for Warm-start Tagging, Ranking & Recommendation - Prabhu, Yashoteja; Kag, Anil; Gopinath, Shilpa; Dahiya, Kunal; Harsola, Shrutendra; Agrawal, Rahul; Varma, Manik (ACM International Conference on Web Search and Data Mining, 2018)
The objective in extreme multi-label learning is to build classifiers that can annotate a data point with the subset of relevant labels from an extremely large label set. Extreme classification has, thus far, only been studied in the context of predicting labels for novel test points. This paper formulates the extreme classification problem when predictions need to be made on training points with partially revealed labels. This allows the reformulation of warm-start tagging, ranking and recommendation problems as extreme multi-label learning with each item to be ranked/recommended being mapped onto a separate label. The SwiftXML algorithm is developed to tackle such warm-start applications by leveraging label features. SwiftXML improves upon the state-of-the-art tree based extreme classifiers by partitioning tree nodes using two hyperplanes learnt jointly in the label and data point feature spaces. Optimization is carried out via an alternating minimization algorithm allowing SwiftXML to efficiently scale to large problems. Experiments on multiple benchmark tasks, including tagging on Wikipedia and item-to-item recommendation on Amazon, reveal that SwiftXML’s predictions can be up to 14% more accurate as compared to leading extreme classifiers. SwiftXML also demonstrates the benefits of reformulating warm-start recommendation problems as extreme multi-label learning tasks by scaling beyond classical recommender systems and achieving prediction accuracy gains of up to 37%. Furthermore, in a live deployment for sponsored search on Bing, it was observed that SwiftXML could increase the relative click-through-rate by 10% while simultaneously reducing the bounce rate by 30%.